MATHEMATICAL MODELS OF PERFORMANCE LONG-TERM STRENGTH HEAT-RESISTANT MATERIAL OF AIRCRAFT ENGINES. - Кулик, М.; Кучер, О.; Ковешніков, М.; Дубровський, С.; Петрук, Я. (Science-based technologies, 2011)
The characteristics of the long-term strength of heat-resistant materials ЕІ437БВД, ЖС6К, ЖС6У, ЕП99 and Х18Н10Т are In the article. These characteristics are often used for manufacturing details of the “hot part” of gas turbine engines. Analytically described characteristics can be used for the calculation of estimation of dura-bility of parts of aircraft engines and other power plants working in high and slowly varying temperature condi-tions, as well as in conditions of cyclic “starts and stops”. The advantage of analytical description of the char-acteristics is the possibility of a more accurate interpolation of the load bearing capacity of heat-resistant alloys at intermediate values of temperatures.